Formation of switchable liquid crystal diffraction gratings by polarisation holography - Pantsialeyeva, Yekatsiaryna P.; Kabanova, Olga S.; Melnikova, Elena A. (Journal of the Belarusian State University. Physics, 2023)
Experimental results on realisation and optimisation of conditions for holographic and polarisation-holographic recording of surface anisotropy in thin films of light-sensitive azo dye AtA-2 in order to form electrically switchable diffraction structures in a layer of nematic liquid crystal are presented. The optimum duration of exposure of films of azo dye AtA-2 by an interference pattern of two coherent light beams that provides a maximum value of diffraction efficiency for diffraction orders m = –1 and m = +1 has been found. A possibility of creating switchable diffraction gratings with a spatial period of 1–7 µm and gratings with fork dislocation forming singular light beams (optical vortices) with a specified value of a topological charge is demonstrated. Experimental dependences of diffraction efficiency of diffraction orders m = –1 and m = +1 on the value of applied voltage are presented. The spatial distribution of light field of generated singular light beams has been investigated by optical interferometry technique, and their stability in the range of applied voltages on the cell of 0–10 V has been analysed. The results of the study are of interest in point of view of fabricating devices and systems for controlling the spatial, phase and polarisation structure of laser radiation.